IKLIM ORGANISASI PADA KANTOR BADAN PENDIDIKAN DAN PELATIHAN PROVINSI SUMATERA BARAT - Tedi Abri Yandi (Jurnal Bahana Manajemen Pendidikan, 2013)
This study aimed to describe the organizational climate on Badan Education and Training Agency of West Sumatra Province is seen from the dimensions of the physical environment, freedom, cooperation and familiarity . The population from this research is 60 employee and sample is 58 employee were taken with stratified random sampling techniuqes. The research instrument was a Likert scale questionnaire form which has been in testing the validity and reliable. Data were analyzed using mean score (mean). Results of this research are organizational climate on Education and Training Agency of West Sumatra Province dimensional views of the physical environment, freedom, cooperation and familiarity is good. Kata kunci: Iklim Organisasi